Effect of SkQ1 Antioxidant on Structural and Functional Conditions of The Brain in PostResuscitation Period - M. L. Lovat; M. Sh. Avrushchenko; O. A. Averina; V. V. Pavshintsev; I. V. Ostrova; Y. V. Zarzhetsky; V. V. Moroz; M. V. Egorov (Общая реаниматология)
The aim was to assess the efficacy of mitochondriatargeted antioxidant SkQ1 in prevention of structural and functional abnormalities of brain postresuscitation after cardiac arrest.Materials and methods. Adult male Wistar rats (n=19) underwent cardiac arrest for 7 minutes followed by resuscitation. Nine rats were administered with 500 nmol/kg SkQ1 per os with water for 2 weeks (1 week before and 1 week after resuscitation). A control group consisted of shamoperated animals (n=10). At days 4—6 post operation locomotor activity and anxiety («elevated plus maze» test) and sensorimotor function of limbs («beam walking» test) were examined. Total numbers of neurons per 1 mm of their layer length in vulnerable neuronal populations (cerebellar Purkinje cells and piramidal neurons of hippocampus fields CA1 and CA4) were estimated by histological analysis of the specimens stained with cresyl violet on day 7 postresuscitation. To identify possible mechanisms of SkQ1 action, the immunohistochemical study of a glialderived neurotrophic factor (GDNF) expression in piramidal neurons of hippocampus was performed by indirect peroxidaseantiperoxidase method and antiGDNF primary polyclonal antibodies.Results. Ischemiareperfusion resulted in neuronal loss in all studied brain areas followed by reduction in locomotor activity and development of sensorimotor deficit. SkQ1 prevented development of postresuscitative locomotor and sensorimotor irregularities, significantly reduced Purkinje cells loss, prevented death of piramidal neurons in hippocampal field CA4, but not in CA1. Data demonstrated, that iIn Purkinje cells from resuscitated rats treated with SkQ1 there was a significant increase in number of GDNFpositive neurons, which were more resistant to ischemia (transition of GDNFnegative cells toward the category of cells actively expressing this factor) that promoted their survival postresuscitation.Conclusion. Data confirm the positive effects of SkQ1 on structural and functional status of the brain postre suscitation and suggest possible use of SkQ1 for the prevention or correction of posthypoxic encephalopathies.